Pengembangan Kurikulum Pendidikan Agama Islam pada PAUD Berbasis Agama Islam (Taman Kanak-Kanak Al-Quran) - Sri Widaningsih (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2024)
Indonesia seeks to improve various levels of education. One of these levels is Early Childhood Education (ECE), especially Islamic-based ECE. ECE which is built on IRE does have several privileges, especially in terms of Islamic teaching. This research aims to see how well the Islamic religion-based ECE program is. The method in this research is content analysis. The main data source for this research is the curriculum from various related guidelines. Data was analyzed through several stages, namely unitizing, recording, reducing, and inferring. The study shows that the development of the IRE curriculum in Islamic-based ECE is largely in line with the growth of the ECE curriculum as a whole. However, there are several significant differences, especially in Document 1 where the development is more focused on the basic or main spirit, namely Islam based on the Qoran and hadith, where everything is integrated and becomes the main part of the implementation process, while IRE in general ECE is part of the development program which its weight is not large and its nature is only support or enrichment.